Estudio doctrinario y comparado de los gota a gota una modalidad de préstamo informal y sus consecuencias asociados al delito de usura. - Medina Rivas., Sandy Paola (2023)
The present degree work is entitled: “Doctrinal and comparative study of drop by drop, a modality of informal loan and its consequences associated with the crime of usury”. His interest in investigating and carrying out a doctrinal and comparative analysis about usury, under this new modality known as “drop by drop”, has currently been showing a significant increase in the informal economy in the country, a factor that affects the social sector, as well as the economic one, since they mobilize large capital resources and are exercised by unscrupulous people who fill their pockets using the need and urgency of resources of thousands of unsuspecting people, in the world and especially in developing countries, They have been vulnerable to the importation of this type of crime, the loan of money to the “chulco” an illicit business with a long history. With the passage of time, this type of business continues to boom and has grown, which is why it constitutes a latent problem whose control cannot be postponed; They are microcredits whose interest rate can be up to five times what is regulated for financial institutions, credit cards, or other types of credit; with cancellation required in daily, weekly or monthly installments and very few access requirements. It has been identified that around 30% of Ecuadorian families have gone to chulqueros at some point. The drop by drop offers advantages such as not asking for a guarantor, which basically delivers the money in cash without asking for guarantees from the debtor. The economic crisis, the lack of access to regular credit, the lack of financial education, has caused a large number of people to access these loans on more than one occasion. Ecuador was the first country in Latin America to import 'drop by drop' loans in 2008, thus also linking them to money laundering, according to data from Police Intelligence agencies in Colombia. At the end of the 1990s, the 'drop by drop' phenomenon was born in the city of Medellín, cradle of one of the largest drug trafficking cartels, where a countdown began for many low-income people in Latin America, since When asking for loans they ended up suffocating from the pressure or paying for their death in installments. Laundering all the money that entered Colombia as profits from drug trafficking was impossible. This is how the figure that today walks the streets of Latin American countries appeared: the 'gota a gota', 'chulco' or 'pay daily', a modality created for money laundering, but which condemns the most vulnerable to financial slavery. poor people of the continent, this name has become popular in most Latin American latitudes given that the leaders of these criminal networks are Colombians who have expanded this practice, which according to judicial institutions in each country, is closely linked to drug trafficking, 6 although it is impossible To specify the dimension of this phenomenon, a study has been carried out that can decipher a mobilization around a million dollars. Local lenders have tried to ensure that their modus operandi is the same in all countries. The 'daily loan' groups recruit young people in Colombia who want to feed the network in other countries and on commercial flights they arrive at their destinations, sometimes with the endorsement of corrupt immigration authorities. There they set up front companies and offer low-income, unbanked people amounts of money at high interest that must be paid daily and delivered immediately. When several people were asked about the reason that prompted them not to make their loans at a financial institution, they simply responded: “the chulqueros give us the money quickly and without so much paperwork.” This shows that people, due to emerging needs, go to these illegal lending centers, without considering the consequences. The modus operandi of these lenders; They offer loans to owners of commercial premises or debtors, in some cases the victims to receive the money sign blank letters as a condition of the chulqueros, the collection is generally done door to door on a motorcycle with an interest that ranges between 10 to 15% monthly, by not paying the lenders they take part of their merchandise, beat the debtors and even threaten their families, 'drip' loans are offered by people or firms with no more structure than an email address or a phone number; used as an advertising channel; notices on posts, walls, sidewalks, etc. Advertisements in markets, businesses and others, through social networks (Facebook, Twitter, Instagram, etc.). The criminal gangs behind the 'drop by drop' loans as they are forged in society, once their victim has been studied and identified, will offer them money to 'improve' their economic conditions, however, they could also be pressured to accept. credit even if they don't need or want it. One of the greatest risks of accessing this form of informal and unregulated loans is that lenders, in order to recover their resources, in some cases resort to coercive means that can threaten the integrity of the borrowers, but now at this time where the misinformation, necessity takes over people, certain important aspects linked to these credits are not taken into account or they are simply not taken into account, these informal lenders are linked to more than money laundering with crimes such as extortion , organized crime, drug trafficking, hitmen, as this is an illicit activity; There is no necessary security for people who cannot meet the interest generated by the same loan acquired. Their collections themselves are not the most common, the victim in this type of loan is “trapped” in the middle of a usurious circuit and, in the event of non- compliance, the organization deploys a collection methodology not exempt from violence that 7 includes harassment, threats and to the use of physical violence. It is recommended that you evaluate whether you need a loan, before thinking about acquiring another obligation with a bank or with a lender drop by drop, carefully analyze the situation that may arise. Consider if it is going to be profitable, if the interest charged is worth it and if the expense you are going to make with that item is necessary, because the consequences could be dire.